In conversation with the Editor-in-Chief of the British Dental Journal, Dr. Hancocks, for 150 years of the journal - Salazar Marocho, Susana Maria (2022)
The British Dental Journal will celebrate its 150th anniversary in 2022. Its editor-in-chief, Dr. Hancock, has led this journal for more than 15 years. In the meeting with him by videoconference, he tells us about the achievements, pillars, and challenges that the journal had over the last years to grow and achieve its longevity and success. Dr. Hancock also shares his role and handling of responsibilities in his role as leader of the journal and his joint work with the British Dental Association.